Faizal & Shabana Foundation: a venture philanthropic approach to education. Issue 1 (6th February 2019) - Sahasranamam, Sreevas; Mitra, Sumit
Abstract : Learning outcomes: Learning outcomes are as follows: understand venture philanthropy in India; discuss in what ways venture philanthropy is different from charity; identify the aims of venture philanthropy and the strategy adopted to achieve those objectives; analyze the role of the unique structuring of a venture philanthropy working in tandem with the government to achieve its objectives; identify the nature and source of dilemmas of disengagement from a project by the venture philanthropist; and understand the role of antecedents and outcomes on how a firm views its social impact initiative (in the Indian context). Case overview/synopsis: The Faizal and Shabana Foundation (F&SF) made one of the largest philanthropic investments in Kerala, India for the redevelopment of Government Vocational Higher Secondary School for Girls, Nadakkavu. The foundation applied a strategic approach to their philanthropic investment making it a unique case of venture philanthropy. The uniqueness of this case lies in the fact that, this is one among those rare cases where venture philanthropy has been successfully implemented within a government educational context. This case highlights how a private philanthropic organization went about executing a project and faced several challenges of scaling up the redevelopment model to other government schools. The other salient aspect is that this case delves into the dilemma faced by a philanthropist of either using the existing model for scaling up or adopting a totally different model. Complexity academic level: Undergraduate and postgraduate business management courses. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS: 11: Strategy.